A scalable network-aware virtual machine allocation strategy in multi-datacentre cloud computing environments. (10th May 2019) - Abdelaal, Marwa A.; Ebrahim, Gamal A.; Anis, Wagdy R.
Virtual machine provisioning in multi-datacentre cloud computing environments is a challenging problem. However, most current virtual machine management strategies ignore their effect on cloud network. In this paper, a scalable network-aware resource allocation strategy is proposed that dynamically allocates virtual machines in cloud computing environments while minimising the overall cost. It is mainly utilised at the cloud service provider that has a large number of datacentres. Several important parameters have been taken into consideration that are mainly ignored in previous related studies. Additionally, software-defined network (SDN) has been adopted in the proposed strategy. Simulation studies have been conducted to evaluate the performance of the proposed strategy. Simulation results show a reduction in the utilisation in the valuable upper-layer links in datacentres that resulted mainly because of favouring lower-cost links during virtual machine allocation process. Additionally, the proposed strategy is able to cope with the dynamic nature of the allocation process.